1986
DOI: 10.1063/1.451122
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of a sodium octanoate micelle in aqueous solution

Abstract: Molecular dynamics simulations of a sodium octanoate micelle in aqueous solution are reported. Simple analytical expressions have been used for the interatomic interactions, including a Lennard-Jones term and a Coulombic interaction betwen partial charges on each site. Two different interaction potentials have been investigated, and amphiphilic aggregation is shown to depend strongly on the electrostatic properties of the water model. For both potentials the micelle shows a broad transition region between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
115
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(131 citation statements)
references
References 46 publications
15
115
1
Order By: Relevance
“…By the same time Sundaram et al reported molecular dynamic simulation of the drug norepiniphrine, demonstrating the possible ways of superposing a phenyl ring of a tricyclic antidepressant on the phenyl ring of norepinephrine [39]. Jonsson et al reported molecular dynamics simulations of a sodium octanoate micelle in aqueous solution which results agree perfectly with NMR measurements [40]. In 1988 the first simulation of a protein in explicit water is carried [41].…”
Section: Molecular Dynamic Studiessupporting
confidence: 73%
“…By the same time Sundaram et al reported molecular dynamic simulation of the drug norepiniphrine, demonstrating the possible ways of superposing a phenyl ring of a tricyclic antidepressant on the phenyl ring of norepinephrine [39]. Jonsson et al reported molecular dynamics simulations of a sodium octanoate micelle in aqueous solution which results agree perfectly with NMR measurements [40]. In 1988 the first simulation of a protein in explicit water is carried [41].…”
Section: Molecular Dynamic Studiessupporting
confidence: 73%
“…To provide a correct understanding of how these molecules behave, a description of surfactant aggregates at the molecular level is required. Simple molecular modeling software packages as well as more advanced Monte Carlo simulations [1,2] and molecular dynamics simulations [3][4][5] of surfactant micelles often provide valuable data, such as micelle diameter and aggregation number, which can be compared with those obtained by experimental methods. The aggregation number of surfactant micelles.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for example, the structural and dynamical properties of micellar solutions can be studied using molecular dynamics simulations. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] From these simulations we can also learn about the molecular level structure and dynamics of water in charged environments and its interaction with such charged assemblies.…”
Section: Introductionmentioning
confidence: 99%